Effect of Trataka on Selected Psychomotor Abilities of FemaleAthletes - Ghosal, Amitava; Kabi, Subhankar (International Research Journal of Ayurveda & Yoga, 2024)
Psychomotor ability is an important attribute for mental processing. The main aim of this present study to observe the effect of trataka on selected psychomotor abilities. Total 20 female athletes were selected as subject and further subdivided in two equal groups like Control Group (CN = 10) and Trataka Group (TG = 10). The average age of all the subjects was 23 years. The measurable psychomotor abilities were Simple Reaction Time, Visual Memory, and Hand Eye Coordination, Depth Perception, and Executive Function respectively. These were measured from trusted online website named by Human Benchmark and Cognifit. Trataka training program was planned for 8 weeks for 35 - 60 minutes, 5 days/week and following the principle of progressive method. The data were analysed with the help of Shapiro-Wilk test, Levine’s Test, One Way ANCOVA, Boneferroni Post Hoc comparison. Results of Simple Reaction Time, Visual Memory, and Hand Eye Coordination, Depth Perception showed significant difference at 0.05 level and Executive Function didn’t showed significant difference. From this study it was concluded that the current treatment protocol helps to develop selected psychomotor abilities that positively influence cognitive function.